Current Approach to Mechanical Valve Obstruction - Hüsnü Değirmenci; Eftal Murat Bakirci; Hikmet Hamur; Arif Arısoy; Mücahit Tan (Global Journal of Perioperative Medicine - Peertechz Publications, 2020)
Although mechanical valve obstruction is rare. It is a rather fatal complication. Pannus and thrombus are common in etiopathogenesis. Multibl imaging methods such as transthoracic echocardiography, transesophageal echocardiography, synefluoroscopy and computed tomography are used for diagnosis. Surgical treatment is performed in the pannus. In thrombosis, fibrinolytic or surgical treatment can be performed. In this article, we presented the current approach to mechanical valve obstruction.